Draft of the MEPS and HEPS for Motorcycle Tyre in Thailand - Kengkamon Wiratkasem (2018)
© 2017 The Authors. Published by Elsevier Ltd. The aim of study is to find suitable high energy efficiency standard (HEPS) and minimum energy efficiency standard (MEPS) of pneumatic tyres for motorcycles in Thailand with the engine displacement below 125 cc excluding tyres for racing and off-road purposes. About 17 million pneumatic tyres (90% domestic product) are sold annually. By using the multistage sampling method on 8 groups (142 models), total 61 models were chosen for testing the rolling resistance coefficient (RRC) following ISO 18164:2005. The results of F-test and t-test show that the section width, diameter, tread, brand, load index and highest velocity index of tyres have no effect on RRC. For suitable HEPS and MEPS, it is found that the RRC of tyres should not be exceeded 12 N/kN and 15.5 N/kN, respectively.